2013
DOI: 10.1111/pace.12068
|View full text |Cite
|
Sign up to set email alerts
|

Larger Interventricular Conduction Time Enhances Mechanical Response to Resynchronization Therapy

Abstract: An optimal acute response to CRT can be obtained by positioning the LV lead at the site associated with the maximum RV-to-LV conduction time. A significant correlation appears to exist between RV-to-LV conduction time and the improvement in systolic function with CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…Moreover, individual variations in the conduction delay, which may modify the site of latest activation, may influence the results . Recently, several authors have demonstrated an association between longer conduction time from the right ventricular to left ventricular (RV‐to‐LV) pacing site and positive response to CRT, thus suggesting to adopt this parameter to guide LV lead placement.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, individual variations in the conduction delay, which may modify the site of latest activation, may influence the results . Recently, several authors have demonstrated an association between longer conduction time from the right ventricular to left ventricular (RV‐to‐LV) pacing site and positive response to CRT, thus suggesting to adopt this parameter to guide LV lead placement.…”
Section: Introductionmentioning
confidence: 99%
“…Physiologically, the electrical excitation radiates from the endocardium to the epicardium. Therefore, arrhythmias with an epicardial origin have a higher risk regarding the development of ventricular fibrillation or torsades [6,7]. If you pace the left ventricle from epicardium only, you must be aware of this fact.…”
Section: Discussionmentioning
confidence: 99%
“…The neck of the CS diverticulum is 5-10 mm wide, opens into the CS, and is proximal to the midcardiac vein. 25 The orifice of the diverticula ranges between 2.6 and 15 mm. The smallest and largest surface area was 0.73 cm 2 and 6.45 cm 2 , respectively.…”
Section: Cs Diverticulummentioning
confidence: 99%
“…Pacing site in cardiac resynchronization therapy (CRT) plays a crucial role for hemodynamic benefits and synchronous systolic function. 25 Left lateral wall was assumed the optimal region for lead positioning in previous studies. 28 However, it has been revealed that lateral or posterolateral branch of the CS is not suitable for all patients especially with respect to mechanical response.…”
Section: The Effect Of Cs Diverticulum During Cardiac Resynchronizatimentioning
confidence: 99%
See 1 more Smart Citation